2023
DOI: 10.1051/meca/2022027
|View full text |Cite
|
Sign up to set email alerts
|

Elasto-hydrodynamic lubrication analysis of a porous misaligned crankshaft bearing operating with nanolubricants

Abstract: In this paper, the combined effects of the characteristic size and concentration of inorganic fullerene-like tungsten disulphide nanoparticles (IF-WS2 NPs) or molybdenum disulphide nanoparticles (IF-MoS2 NPs) on the nonlinear dynamic behaviour of a gasoline engine crankshaft bearing subject to an arbitrary force torsor (effective applied force and moment vector) are theoretically and numerically investigated using the V. K. Stokes micro-continuum theory. These NPs are the most common additives for lubrication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Lubrication regime analysis supported by experimental results obtained in study [10] indicated that the correct selection of lubricant and suitable running conditions was very important in the tribological characteristics of porous bearings. In [11], the authors explored two different technological approaches to friction reduction within engines. The first solution is based on treating the active contact surfaces through the deposition of coatings, such as thin layers of amorphous carbon.…”
Section: Introduction and Lubrication Theory Backgroundmentioning
confidence: 99%
“…Lubrication regime analysis supported by experimental results obtained in study [10] indicated that the correct selection of lubricant and suitable running conditions was very important in the tribological characteristics of porous bearings. In [11], the authors explored two different technological approaches to friction reduction within engines. The first solution is based on treating the active contact surfaces through the deposition of coatings, such as thin layers of amorphous carbon.…”
Section: Introduction and Lubrication Theory Backgroundmentioning
confidence: 99%